Ligilactobacillus salivarius LZZAY01 accelerated autophagy and apoptosis in colon cancer cells and improved gut microbiota in CAC mice - Wenhong Yang; Tao Li; Shixiang An; Rong Chen; Yuxin Zhao; Jiaxian Cui; Mingyu Zhang; Jingkun Lu; Yunpeng Tian; Lili Bao; Pengwei Zhao (Microbiology Spectrum)
ABSTRACT Colorectal cancer (CRC) is one of the malignant tumors globally, with high morbidity and mortality rates. The mainstay treatment of CRC includes surgery, radiotherapy, and chemotherapy. However, these treatments are associated with a high recurrence rate, poor prognosis, and highly toxic side effects. The probiotics have the potential to prevent CRC, and they display a favorable safety performance. Probiotics could provide a potential strategy to prevent and treat CRC. The impact of LZZAY01 on cancer cell lines CT-26, HCT-116, and SW-620 was evaluated by conducting cytotoxicity and clonogenicity tests. A model of colitis-associated cancer (CAC) was established in C57BL/6j mice following induction with AOM/DSS. The levels of autophagy and apoptosis proteins, tight junction proteins, and inflammatory factors were detected by western blotting, immunofluorescence assay, and enzyme-linked immunosorbent assay. High-throughput sequencing of gut 16S rRNA was performed to analyze the abundance and diversity of the gut microbiome. LZZAY01, a new strain of Ligilactobacillus salivarius, was certified by an evolutionary tree and average nucleotide identity. LZZAY01 enhanced autophagy and apoptosis in CT-26, HCT-116, and SW-620 cell lines. It preserved the integrity of the intestinal barrier by regulating the tight junction protein ZO-1 and claudin-1. The tumor necrosis factor-α and interleukin-6 were reduced by LZZAY01. The abundance and diversity of the intestinal microbiota were enhanced, especially the beneficial bacterial species maintaining the balance of the intestinal flora such as Bifidobacterium and Lactobacillus. L. salivarius LZZAY01 improved CAC via suppressing the growth of colon cancer cells, promoting autophagy and apoptosis, enhancing intestinal tight junctions, reducing intestinal barrier degradation, modifying the gut microbiota abundance, and decreasing inflammatory reactions.IMPORTANCEAlthough similar probiotics have been shown to have anticancer potential in colorectal cancer (CRC), there is a paucity of research related to the preventive function of probiotics against CRC. And there are fewer studies about the mechanism of probiotics’ preventive effects on CRC. The regulation of tumor cell proliferation and apoptosis by the active ingredients of probiotics may be one of the mechanisms of their prevention of CRC. In this study, we explored the effects of L. salivarius LZZAY01 on autophagy and apoptosis of colon cancer cells in vitro and in vivo and proposed a possible mechanism for the prevention of CRC by probiotics.